2013
DOI: 10.1080/20445911.2013.812093
|View full text |Cite
|
Sign up to set email alerts
|

Parallel language activation and cognitive control during spoken word recognition in bilinguals

Abstract: Accounts of bilingual cognitive advantages suggest an associative link between cross-linguistic competition and inhibitory control. We investigate this link by examining English-Spanish bilinguals’ parallel language activation during auditory word recognition and nonlinguistic Stroop performance. Thirty-one English-Spanish bilinguals and 30 English monolinguals participated in an eye-tracking study. Participants heard words in English (e.g., comb) and identified corresponding pictures from a display that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
158
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(183 citation statements)
references
References 84 publications
(163 reference statements)
21
158
4
Order By: Relevance
“…For bilingual listeners, auditory input in one language activates possible word candidates regardless of language membership (e.g., Marian & Spivey, 2003a, 2003b). This input-driven language co-activation is observed across different proficiency levels, ages of onset of language acquisition, and highly diverse language pairs (e.g., Blumenfeld & Marian, 2007, 2013; Canseco-Gonzalez et al, 2010; Cutler, Weber, & Otake, 2006; Ju & Luce, 2004; Marian, Blumenfeld, & Boukrina, 2008; Weber & Cutler, 2004). Resolving such cross-linguistic competition has been posited to require cognitive inhibition skills (e.g., Green, 1998; Shook & Marian, 2013).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…For bilingual listeners, auditory input in one language activates possible word candidates regardless of language membership (e.g., Marian & Spivey, 2003a, 2003b). This input-driven language co-activation is observed across different proficiency levels, ages of onset of language acquisition, and highly diverse language pairs (e.g., Blumenfeld & Marian, 2007, 2013; Canseco-Gonzalez et al, 2010; Cutler, Weber, & Otake, 2006; Ju & Luce, 2004; Marian, Blumenfeld, & Boukrina, 2008; Weber & Cutler, 2004). Resolving such cross-linguistic competition has been posited to require cognitive inhibition skills (e.g., Green, 1998; Shook & Marian, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Mercier, Pivneva, & Titone, 2014). In a more recent study, Blumenfeld and Marian (2013) showed that efficient conflict resolution was indeed associated with how unimodal bilinguals manage between-language activation during auditory word recognition (also see Mercier et al, 2014). For Spanish-English bilinguals, better performance on a nonlinguistic spatial Stroop task was associated with increased cross-linguistic activation during the early stages of word recognition (300-500 ms after word-onset) and decreased cross-linguistic activation during later stages of word recognition (633-767 ms after word-onset).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Extensive research has been conducted about some of the factors underlying individual differences among L2 learners (Dörnyei, 2005). Among them, cognitive variables such as working memory (Miyake & Friedman, 1998), attention (Segalowitz & Frenkiel-Fishman, 2005), inhibitory control (Blumenfeld & Marian, 2013;Mercier, Pivneva, & Titone, 2013), vocabulary size (Majerus, Poncelet, Van der Linden, & Weekes, 2008), and processing speed (Golestani, Molko, Dehaene, LeBihan, & Pallier, 2007) have been associated with higher L2 proficiency and more efficient L2 processing (see also Costa & Santesteban, 2004;Festman, Rodriguez-Fornells, & Münte, 2010;Rodriguez-Fornells, Balaguer, & Münte, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…However, are variations in levels of activation a sufficient mechanism to account for the pattern of language use in the corpus data? Experimental evidence indicates that even when only one language is in play, lexical representations and grammatical constructions are active in the other language and lexical representations reach to the level of phonological form (e.g., (Blumenfeld and Marian 2013;Christoffels et al 2007;Costa et al 2000;Hoshino and Thierry 2011;Kroll et al 2015) for a review). Given the corpus data cited above, top-down processes of control must allow speakers to produce words and constructions in just one language in a code-switching context despite parallel activation of words and constructions in the other language (for further discussion of bottom-up and top-down processes of language control, see (Kleinman and Gollan 2016;Morales et al 2013)).…”
Section: Introductionmentioning
confidence: 99%